2014
DOI: 10.1002/pd.4345
|View full text |Cite
|
Sign up to set email alerts
|

Validation of automatic scanning of microscope slides in recovering rare cellular events: application for detection of fetal cells in maternal blood

Abstract: Automatic scanning was more efficient and consistent than manual scanning for detection of rare FCs and required considerably less operator time. Automatic scanning using FISH is more sensitive than that using PRINS. The study validates automatic scanning retrieval of FCs from maternal blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Attempts to recover male fnRBCs in blood samples obtained prior to CVS or pregnancy termination from women carrying male pregnancies failed in 60–70% of cases leaving some doubt as to whether this cell type is present in sufficient numbers for routine analysis during the first trimester. In contrast, two groups have demonstrated that there are one to six fetal cells per milliliter of mother's blood during the first trimester using very reliable methods for Y chromosome FISH, and showed that these cells are certainly or most likely trophoblasts. Based on these reports, we have focused exclusively on detecting trophoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to recover male fnRBCs in blood samples obtained prior to CVS or pregnancy termination from women carrying male pregnancies failed in 60–70% of cases leaving some doubt as to whether this cell type is present in sufficient numbers for routine analysis during the first trimester. In contrast, two groups have demonstrated that there are one to six fetal cells per milliliter of mother's blood during the first trimester using very reliable methods for Y chromosome FISH, and showed that these cells are certainly or most likely trophoblasts. Based on these reports, we have focused exclusively on detecting trophoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study published by Drouin et al looked at the validation of automatic scanning of microscopic slides to detect fetal cells in maternal blood [56]. The frequency of fetal cells per 1 ml of maternal blood identified by this approach ranged from 3 to 6 cells in normal pregnancies and 13 to 21 cells in Down syndrome pregnancies.…”
Section: Type and Number Of Fetal Cells In The Maternal Circulationmentioning
confidence: 98%
“…Our findings provide a proof for the feasibility of NIPD from very small numbers of fetal cells and suggest that detection, amplification and analysis of as few as 5 fetal cells that could be obtained from 2-3 ml of maternal peripheral blood [45] can sufficient enough to provide an accurate NIPD. The few fetal cells required together with the use of automatic scanning for the detection of fetal cells [73] and SCs-WGA will help to overcome the problem of rarity of these cells in the maternal blood and make their use in NIPD much more easily achievable. Although this method is not yet completely mature due to the absence of a perfect antigen that can recognize 100% of fetal cells, relentless efforts continue and should lead to the development of this antigen in the near future [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…QF-PCR, which is less expensive and almost entirely automated, enables more women to undergo prenatal diagnosis without a significant increase in health expenditure [37,38,71,72]. The use of innovative technology like automatic cellular scanning of slides for the detection of fetal cells from maternal peripheral blood, which we have recently optimized and used for detection and quantification of fetal cells in the maternal blood in euploid and aneuploid pregnancies, will help to avoid the traditional cumbersome and time-consuming manual detection of rare fetal cells from maternal blood [73]. …”
Section: Discussionmentioning
confidence: 99%